2019
DOI: 10.1039/c8mt00374b
|View full text |Cite
|
Sign up to set email alerts
|

Designating ligand specificities to metal uptake ABC transporters in Thermus thermophilus HB8

Abstract: Acquisition of different metal ions by metal uptake ABC transporters of Thermus thermophilus HB8 for accomplishing its various cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Heavy metal transport proteins play a key role in microbiological metabolism under Cd stress. In particular, ATP binding cassette transporters (ABC transporters) responsible for maintaining metal ion homeostasis by transporting metal ions across the cell membrane, either as naked ions or in the form of various complexes [20,21]. In this work, 7 ABC transporters were identified in M. spongiola; their mean change in expression was 1.006< log 2 FC <15.776 (Table S6).…”
Section: Expression Of Transporter Proteins In M Spongiola Under Cd Stressmentioning
confidence: 82%
See 1 more Smart Citation
“…Heavy metal transport proteins play a key role in microbiological metabolism under Cd stress. In particular, ATP binding cassette transporters (ABC transporters) responsible for maintaining metal ion homeostasis by transporting metal ions across the cell membrane, either as naked ions or in the form of various complexes [20,21]. In this work, 7 ABC transporters were identified in M. spongiola; their mean change in expression was 1.006< log 2 FC <15.776 (Table S6).…”
Section: Expression Of Transporter Proteins In M Spongiola Under Cd Stressmentioning
confidence: 82%
“…In this study, a large number of transporter genes were remarkably induced in different Cd-treatment groups, including 7 ATP binding cassette transporter (ABC transporter), 3 Multidrug resistance protein (MRP), 4 Copper transporter (CTR), 4 Zinc transporter (ZRT), 3 Heavy metal transporter (HMT), 1 Cation transport ATPase (CE) and 1 Iron transport multicopper (ILT) (Table S6). ABC transporters, as one of the largest families of microbial membrane proteins, shows great important in resisting virulence and drug, especially in the function of maintaining metal ion homeostasis by transporting metal ions across the cell membrane in ionic/complex forms [20,21]. It was reported that the expression of 3 ABC genes (EpABC2.1, EpABC3.1, or EpABC4.1) of dominant dark septate endophytes (DSEs) could promote the restoring growth of metal-sensitive mutant by alleviating the inhibitory activity in yeast caused by Pb, Zn and Cd, and further altered toxic ions uptake and accumulation [27].…”
Section: Mechanisms Of CD Stress Resistance In M Spongiolamentioning
confidence: 99%
“…Thermophilic microorganisms are capable of surviving in diverse habitats such as geothermal springs, volcanic areas, hot water regions, marine hydrothermal vents and geothermal power plants (Ranawat & Rawat, 2018). Such punitive environments rich in metal, metalloid and metal-ion complexes necessitate the availability of specific metal-uptake transporters in the microorganisms (Mandal et al, 2019). Among the various functions of divalent metal ions in cellular and physiological processes, one of the important functions is to stimulate the uptake of citrate molecules in prokaryotes (Krom et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thermus thermophilus is one such well studied Gram-negative thermophilic bacterium that resides in marine hot springs and can grow at temperatures of $50-82 C (Alarico et al, 2005;Ohtani et al, 2012). Previously, using an in silico analysis we have reported the presence of an Mg 2+ /Fe 3+ -complexed citrate-transport system in T. thermophilus HB8 (Mandal et al, 2019). In this study, we confirm the presence of a divalent metal ion-stimulated citrate-binding protein (ORF TTHB177; hereafter referred to as metal ion citrate transporter A, MctA).…”
Section: Introductionmentioning
confidence: 99%
“…
Nearly one-third of the proteins require metal ions to accomplish their functions, making them obligatory for the growth and survival of microorganisms in varying environmental niches [1,2]. In prokaryotes, besides their involvement in various cellular and physiological processes, metal ions stimulate the uptake of citrate molecules.
…”
mentioning
confidence: 99%